Antihyperlipidemic Activity of Hydroxyl Methylglutaryl Coenzyme A Reductase Inhibitor on Lipid Profile in Secondary Hyperlipidemia - Naveed Ali Siddiqui; Naheed Akhtar; Ayesha Shahid; Fatima Bint Taj; Ayesha Ayaz; Zulfiqar Ali Moosa; Farooq Azeem (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objectives: To observe the variations in lipid profile in patients with secondary hyperlipidemia using HMG-CoA reductase inhibitor. Methods: This study was done at private hospital in patients predominantly suffering from secondary hyperlipidemia. The duration of study was about 4 months. Body weight, height and blood pressure of subjects were assessed. The subjects were asked to answer the related question on cigarette smoking, health related complaints, detailed history of family, drug usage, and nutritional habits. Subjects were requested to make up a permission form before starting the research study. This case control study was performed at local private Hospital, located at Karachi from 1st April 2017 to 30th July 2017. The aim of research was to analyze the effects of HMG-CoA reductase inhibitor on lipid profile in patients of secondary hyperlipidemia. Age between 35 to 65 years and secondary hyperlipidemic patients were included in the inclusion criteria. Lactating/pregnant women, renal, liver and established coronary artery diseases were included in exclusion criteria. Results: Sixty patients having deteriorated lipid profile were included in this research (age 30-60 years). Subjects were prescribed simvastatin orally 20 mg/day (international product) for 04 months. The total cholesterol, triacylglycerol, LDL and HDL were analysed using simvastatin (20mg/day) of international standard in the serum of secondary hyperlipidemic patients. Conclusion: During this study it is observed that Simvastatin raises the HDL level and reduces LDL level and cholesterol level.